Research on the Effect of New Basic Science Programs to High Quality Faculty HCMCUTE Students - Nguyen , Hồng Nhung (Journal of Technical Education Science, 2018)
From 2015 – 2016 academic year, at High Quality Faculty, HCMC University of Technology and Education, the study program included Mathematics, Physics and Chemistry, that was taken from the developed countries, were taught for students as basic science. The database analyse such as independent samples t-test, normal distribution test, bootstrap method and regression with dummy variables were used for this research. The outcome of this research are the conclusions about the effect of new basic science program to High Quality Faculty students compared with the prior program. The data used for the analysis were taken from students of HCMC University of Technology and Education in the 2015 – 2016 academic year. Statiscal conclusions are given by the SPSS data analysis software.